PELAKSANAAN PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS TUNANETRA MELALUI PEMBELAJARAN DI SLB NEGERI 1 BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Sry Maisara; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to find out how formal education is for students with special needs who are blind. Among them are blind children who are located in the Rokan Hilir Regency, precisely in BaganSiapi-api City. Next, we want to know the implementation of education for children with special needs for the blind. This study uses a descriptive qualitative research method. Data collection is done by observation, interviews and documentation. Interviews were conducted with teachers, school principals and parents, especially the student's mother. The results of the study show that the pattern of implementing education through learning can be seen in the field or cognitive domain of the child, namely: being able to understand material, in the affective domain can help in forming attitudes, and the psychomotor domain can help children in developing children's skills. There is support from family institutions, namely assistance in the form of education from parents of children with special needs for the blind. Keywords: Implementation of Education, Children with Special Needs, Family